Puterylicious Delight / Nurul Aida Mat Ridzuan - Mat Ridzuan, Nurul Aida (2021)
In online business, getting the customer attention to the product is most important part in increase the sale. The report describes on how to promote the product to gain the customer attention with few techniques. The techniques are making a teaser of the product, soft sell and hard sell. Teaser is purpose of the teaser is to make the potential customer feel curious on what we sell. Soft sell is telling the story about the product to make the potential customer invested to follow up with the product. Hard sell is advertising the product right a way and make the customer make the decision of buying for short time. With these techniques, people will attract to the product.